2014
DOI: 10.1016/j.clay.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of pentachlorophenol to a humin-like substance–bentonite complex prepared by polycondensation reactions of humic precursors

Abstract: > HuLS-bentonite complex was prepared via polycondensation of humic precursors. > HuLS had more aliphatic character than HaLS that was a water-soluble fraction. > XRD patterns demonstrated the intercalation of HuLS into the bentonite. > The prepared HuLS-bentonite complex had a strong affinity to pentachlorophenol. > *Highlights (for review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The O/C, H/C, and C/N atomic ratios (Table 2) based on elemental analysis, have been used to describe the content of oxygenated groups in the molecules, the degree of aromatic ring condensation, and the nitrogen content, respectively (Giovanela et al, 2010;Stevenson, 1994). In general, HA showed higher O/C ratios than those of HLA, suggesting a greater abundance of oxygen-containing functional groups (Fukushima et al, 2014). The H/C ratio showed that HA, except for the TM II HA, have higher condensation of aromatic rings than do HLA; lower C/N atomic ratios for HA suggest more nitrogen-containing structures (F. .…”
Section: Characterization Of Humic Acids and Humic-like Acidsmentioning
confidence: 95%
“…The O/C, H/C, and C/N atomic ratios (Table 2) based on elemental analysis, have been used to describe the content of oxygenated groups in the molecules, the degree of aromatic ring condensation, and the nitrogen content, respectively (Giovanela et al, 2010;Stevenson, 1994). In general, HA showed higher O/C ratios than those of HLA, suggesting a greater abundance of oxygen-containing functional groups (Fukushima et al, 2014). The H/C ratio showed that HA, except for the TM II HA, have higher condensation of aromatic rings than do HLA; lower C/N atomic ratios for HA suggest more nitrogen-containing structures (F. .…”
Section: Characterization Of Humic Acids and Humic-like Acidsmentioning
confidence: 95%
“…Likewise, it has been found that NOM also has the ability to interact with the surface of many adsorbents, affecting both selectivity and working adsorption capacities [35,[45][46][47].…”
Section: -90%) and Contains A Heterogeneous Mixture Of Molecules Wimentioning
confidence: 99%
“…This could be attributed to the heterogeneous mixed character of the acid macromolecules, which have the ability to interact effectively with not only the surface of these IOCs (as previously discussed), but with the phenols. Some studies have shown that indeed there exists a synergistic effect between the uptake of HA, aromatic compounds and adsorbents, in which the acid acts as a "bridging molecule" between the latter two [38,45,63,64]. For instance, Basly and coworkers have shown that there is an increase in the adsorption of cationic dyes in the presence of HA as co-adsorbate onto iron surfactantmodified pillared montmorillonites [38].…”
Section: Adsorption In the Presence Of Humic Acidmentioning
confidence: 99%
“…However, the degree of contribution may be dependent on the state of organic matter in soil. For example, PCP sorption on the surface of clay mineral is smaller than that on the intercalated organic matter between layers [26]. Significantly low PCP K F (0.13) in "organic free" had been reported as compared with native soil (43.10) [58].…”
Section: Sorption Isotherm and Modelingmentioning
confidence: 97%
“…Some studies have shown that at typical environmental pH values (pH [7][8], several chlorophenols, including PCP are usually present in both molecular and phenolate form. Thus, their sorption is pH-dependent [21][22][23][24][25][26]. Correlation between sorbent organic matter contents and sorption capacity of ionized and neutral chlorophenols is well documented [21,27,28].…”
Section: Introductionmentioning
confidence: 99%